PENGUATAN PROFIL PANCASILA TEMA GAYA HIDUP BERKELANJUTAN MELALUI PEMANFAATAN SAMPAH SDN 4 CAKRANEGARA - Jannah, Miftahul (Al-mujahidah, 2024)
The problem of waste is very often found in Indonesia. Instilling an attitude of caring for the environment from an early age is very necessary. Therefore, this article aims to describe activities to strengthen the Pancasila profile with the theme of a sustainable lifestyle through the use of waste in order to foster creativity and an attitude of caring for the environment in students. The activity was carried out with training in making poster frames from cardboard. The results of the implementation of the project to strengthen the profile of Pancasila students (P5) at SDN 4 Cakranegara show that the activity was carried out well and received quite good enthusiasm from the students. Through project activities to strengthen the profile of Pancasila students (P5), students can grow and strengthen the character of the Pancasila student profile in students, especially working together, reasoning critically and creatively. Not only that, students become more aware and care about the surrounding environment.